2011
DOI: 10.1186/1752-1947-5-236
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary interstitial emphysema presenting in a woman on the intensive care unit: case report and review of literature

Abstract: IntroductionPulmonary interstitial emphysema is a life-threatening form of ventilator-induced lung injury. We present one of the few reported adult cases of pulmonary interstitial emphysema in a woman with respiratory failure admitted to our intensive care unit.Case presentationAn 87-year-old Caucasian woman with a diagnosis of community-acquired pneumonia was admitted to our intensive care unit requiring invasive ventilation. The combination of a poor oxygenation index and bilateral alveolar/interstitial infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 9 publications
0
19
0
2
Order By: Relevance
“…PIE is a potentially life-threatening condition wherein air collects in the pulmonary interstitium [16]. Although PIE commonly occurs in neonates but rarely in adults [16,49].…”
Section: Pie (V-1)mentioning
confidence: 99%
See 4 more Smart Citations
“…PIE is a potentially life-threatening condition wherein air collects in the pulmonary interstitium [16]. Although PIE commonly occurs in neonates but rarely in adults [16,49].…”
Section: Pie (V-1)mentioning
confidence: 99%
“…PIE is a potentially life-threatening condition wherein air collects in the pulmonary interstitium [16]. Although PIE commonly occurs in neonates but rarely in adults [16,49]. Greenough et al [50] reported that the incidence and mortality rates of PIE in preterm infants who required ventilation for respiratory distress syndrome (RDS) were 19.5% and 24%, respectively [50].…”
Section: Pie (V-1)mentioning
confidence: 99%
See 3 more Smart Citations